Risk analysis of CNG dispensing unit by fuzzy digraph matrix and Dempster-Shafer approach. (8th October 2019) - Srivastava, Priyank; Khanduja, Dinesh; Ganesan, Subra; Agarwal, Mohit; Tulsiyan, Mridul; Tandon, Manik; Gupta, Sumit
The CNG dispensing unit is an important investment for taking advantage of CNG fuel, though its handling is not as simple as other conventional fuels. The cost can only be realised if it is operated with maximum availability. In present research work, risk analysis of CNG dispensing unit has been exemplified by applying fuzzy digraph matrix and D-S theory. Forty-three failure causes have been identified, analysed and prioritised using the mentioned approach. The display error and regulator function failure for metering skid, internal valve failure and gasket damage for compressor, internal pipe leakage and PLC failure for priority panel, flow sensor, motherboard and valve failure for dispenser unit, plug and tank leakage have been identified as risk for CNG dispensing unit. The results from both the approaches show synergy. The risk identification and prioritisation results have been forwarded to maintenance engineer for critical analysis and proper maintenance planning.